In silico analysis of six known Leishmania major antigens and in vitro evaluation of specific epitopes eliciting HLA-A2 restricted CD8 T cell response. - Negar Seyed; Farnaz Zahedifard; Shima Safaiyan; Elham Gholami; Fatemeh Doustdari; Kayhan Azadmanesh; Maryam Mirzaei; Nasir Saeedi Eslami; Akbar Khadem Sadegh; Ali Eslami Far; Iraj Sharifi; Sima Rafati (Public Library of Science (PLoS), 2011)
BACKGROUND: As a potent CD8(+) T cell activator, peptide vaccine has found its way in vaccine development against intracellular infections and cancer, but not against leishmaniasis. The first step toward a peptide vaccine is epitope mapping of different proteins according to the most frequent HLA types in a population. METHODS AND FINDINGS: Six Leishmania (L.) major-related candidate antigens (CPB,CPC,LmsTI-1,TSA,LeIF and LPG-3) were screened for potential CD8(+) T cell activating 9-mer epitopes presented by HLA-A*0201 (the most frequent HLA-A allele). Online software including SYFPEITHI, BIMAS, EpiJen, Rankpep, nHLApred, NetCTL and Multipred were used. Peptides were selected only if predicted by almost all programs, according to their predictive scores. Pan-A2 presentation of selected peptides was confirmed by NetMHCPan1.1. Selected peptides were pooled in four peptide groups and the immunogenicity was evaluated by in vitro stimulation and intracellular cytokine assay of PBMCs from HLA-A2(+) individuals recovered from L. major. HLA-A2(-) individuals recovered from L. major and HLA-A2(+) healthy donors were included as control groups. Individual response of HLA-A2(+) recovered volunteers as percent of CD8(+)/IFN-γ(+) T cells after in vitro stimulation against peptide pools II and IV was notably higher than that of HLA-A2(-) recovered individuals. Based on cutoff scores calculated from the response of HLA-A2(-) recovered individuals, 31.6% and 13.3% of HLA-A2(+) recovered persons responded above cutoff in pools II and IV, respectively. ELISpot and ELISA results confirmed flow cytometry analysis. The response of HLA-A2(-) recovered individuals against peptide pools I and III was detected similar and even higher than HLA-A2(+) recovered individuals. CONCLUSION: Using in silico prediction we demonstrated specific response to LmsTI-1 (pool II) and LPG-3- (pool IV) related peptides specifically presented in HLA-A*0201 context. This is among the very few reports mapping L. major epitopes for human HLA types. Studies like this will speed up polytope vaccine idea towards leishmaniasis.